Relationship Between Child Perfectionism and Psychological Disorders - Lozano, Luis Manuel; Valor-Segura, Inmaculada; García-Cueto, Eduardo; Pedrosa, Ignacio; Llanos, Alexia; Lozano, Luis (Frontiers in Psychology, 2019)
Objective. Perfectionism is one of the variables related to the correct emotional development or with the appearance of clinical symptomatology in childhood. A study has been designed to evaluate the differential effect that each dimension of perfectionism (External Pressure, Self-Exigency, and Negative Self-Evaluation) has in a Spanish children sample of general population for each of the following clinical aspects: irritability, worthlessness feelings, thinking problems and psychophysiological symptoms. Method. By a random cluster sampling, a total of 2636 children from 8 to 12 years (M= 9.9, SD= 1.2; 51.3% boys) took part in this research. A serial multiple mediators model was used to check the relation between External Pressure over the clinical symptoms through Self-Exigency and Negative-Self Evaluation. Results. The results have shown a predictive effect of External Pressure over a great variety of clinical symptomatology (irritability, worthlessness, thinking problems and psychophysiological symptoms), a relation mediated by Self-Exigency and Negative Self-Evaluation. These relations suggest that External Pressure and Negative Self-Evaluation are maladaptive dimensions as they predict the appearance of symptomatology, being the level of Self-Exigency a protective dimension and favoring the child’s positive development. Conclusions. In consequence, these results point to the importance of the study of these variables that can generate difficulties in childhood in order to improve children’s quality of life and their correct development. Keywords​: Perfectionism, Clinical symptomatology, Childhood, Mediation analyses, Childhood Perfectionism Inventory